ANALISIS POLA PENJUALAN HASIL KOMODITI PADI SAWAH DI DESA RIAS KECAMATAN TOBOALI KABUPATEN BANGKA SELATAN - Sela Oktia; Iwan Setiawan; Fournita Agustina (Journal of Integrated Agribusiness, 2020)
The purpose of this research describe patterns of sale of a commodity rice paddy fields in the village of the District Rias Toboali South Bangka Regency, to analyze factors influencing farmers decision in choosing the pattern of sales of commodities in the form of paddy rice grain and rice in the village Rias Toboali District of South Bangka district, analyze the differences in the income of farmers who chose the sales pattern in the form of grain and rice in the village Rias Toboali District of South Bangka Regency. The research was conducted on In June 2019 until January 2020 Village Rias Toboali District of South Bangka Regency. The method used is survey method. The sampling method used is incidental sampling with a sample of two groups of farmers who undertake different sales pattern (grain and rice). The number of samples in the form of farmers who sell grain as many as 35 people and the number of samples in the form of farmers who sell rice about 35 people. Methods of data analysis using Descriptive statistics, quantitative analysis (binary logistic regression, Compare independent samples t-test), The results showed patterns of sale of a commodity rice paddy fields in the village of the District Rias Toboali South Bangka Regency in the form of paddy rice grain and rice. The variables influencing the farmer's decision to choose the pattern of sales of grain and rice that age, the level of producer prices and capital owned with a value of Nagelkerke R Square 84,2%. There are differences in income average grain Rp.4,725,751.43 and income of rice farmers Rp.13,040,380.00 with margin ranges of grain and rice sales revenue in the amount of Rp.8.314.629.